13.3k views
1 vote
Solve the equation... -6t+27=5t-12+t ???

Solve the equation... -6t+27=5t-12+t ???-example-1
User Cloned
by
6.1k points

2 Answers

1 vote
I’m going to combine like terms first.
5t + t - 12 = 6t - 12
Next we’re going to leave all the constants on one side and the variables on the other. To do this, we’re going to add/subtract the constants on both sides.
-6t - 6t = -12 - 27
-12t = -39
Isolate t
-39/-12 = 3.25
Since we divided the negative out of t, t is now positive.
T = 3.25
User Jaybeeuu
by
5.7k points
6 votes

Answer:


Explanation:

-6t + 27 = 5t - 12 + t

Collect like terms

-6t + 27 = 6t - 12

Add 6t to both sides

27 = 12t - 12

Add 12 to both sides

39 = 12t

Divide 12 to both sides

39/12 = t

Simply

t = 13/4


User Richard Benson
by
6.2k points